ANACARDIUM OCCIDENTALE L.: ação sobre a inibição enzimática, glicemia e produção de insulina na diabetes - SILVA, Tonicley Alexandre da (2015)
Diabetes mellitus is a chronic disorder affecting the metabolism of carbohydrates, fats and proteins, leading to hyperglycemia, due to reduced sensitivity, or insufficient insulin production. Plant species are often used by the population as a complementary treatment of diabetes among the most cited epecies is Anacardium occidentale L. This study evaluated the effect of hydroalcoholic extract of Anacardium occidentale L. and compounds on the α-amylase and α-glucosidase in vitro and the effects of A. occidentale on the production of insulin and blood glucose levels in murine diabetes. For this systematized up the information on scientific and ethnobotanical data on the anti-diabetes activity A. occidentale, considering the toxicity and pharmacological effects. We evaluated the effect of the aerial parts of A. occidentale and its major compounds (anacardic acid, shikimic, gallic and ellagic) on inhibition of α-glucosidase and α-amylase enzymes in vitro. Evaluated the effect of the extract of A. occidentale flowers in controlling type 2 diabetes, considering the production of glucose, insulin, and in vivo cytokines. To achieve the in vitro assays hydroalcoholic extracts of flowers were prepared (EFL), leaves (EF) and shell (EC) stem of A. occidentale, preparations containing compounds present in the extracts as well as mixtures of such compounds: anacardic acid (AA ), shikimic (AC), gallic (AG) and ellagic (AE) tested in various concentrations (0.5, 5, 50 and 500 mg/Kg). In vitro assays have evaluated the effect of extracts and compounds on the inhibition of α-amylase and human salivary α-glucosidase from Saccharomyces cerevisiae. To conduct in vivo testing diabetes was induced in male Swiss mice, three months old, with fructose and streptozotocin. The animals were divided into 6 groups of 5 animals each, treated with saline, metformin and EFL in concentrations of 0.5; 5; 50 and 500 mg/Kg evaluated by oral tolerance test glucose, glycemic variation, consumption of water and feed, changes in body weight, concentration of glycated hemoglobin, insulin, frutosaminas, triglycerides, total cholesterol and HDL and LDL fractions, production of cytokines IFN-, TNF-, IL-4 and IL-10. The in vitro results showed that the EFL showed the highest inhibitory effect on the activity of α-amylase and α-glucosidase than the other extracts enzymes even at low concentrations, possibly due to the presence of anacardic acid and ellagic acid, since these two compounds present in the crude extract, when evaluated alone, or in combination with shikimic acid showed a similar effect to the EFL. In vivo the EFL reduced the glycemic peak, consumption of water and feed, the concentration of glycated hemoglobin, frutosaminas, triglycerides, total cholesterol and LDL. On the other hand, occurred in the same group increase in the HDL fraction, and increase in the concentration of anti-inflammatory cytokines IL-10 and IL-4. Together, the results indicate that the EFL with proven effectiveness in controlling diabetes mellitus due to enzyme inhibition, and reducing glucose homeostasis in insulin production, possibly due to the increase in peripheral sensitivity.